Amelia Bedelia by the yard - Parish, Herman; Avril, Lynne, 1951- (New York : Greenwillow Books, an imprint of HarperCollinsPublishers, 2016)
"Amelia Bedelia's mother loves garage sales so much, she decides to have one herself! But Amelia Bedelia loves her garage and does not want to sell it, so she and her parents decide to call it a yard sale instead. People come from all over the neighborhood to buy Amelia Bedelia and her parents' old things, and one woman even buys the yard!"--
"1, beginning reading."
Keywords: Mothers and daughters -- Juvenile fiction; Garage sales -- Juvenile fiction; Humorous fiction